Kemandirian belajar jarak jauh bidang studi matematika selama pandemi Covid-19: studi kasus di SMA swasta di NTT - Bhoki, Maria Yasinta (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
Independence is one of the important factors that influence student learning success. From the independence of learning that students have, it will bring positive attitude changes in every action they take. This study aims to analyse the level of student learning independence in mathematics during the Covid-19 pandemic. The research method includes descriptive quantitative, with a sample of 104 people in the study. Data collection was carried out by distributing questionnaires through google form so that it was easily accessible by students and teachers. The data analysis technique used in this study is to calculate the percentage of each aspect in the parameter, then interpret the data percentage score, and analyse each aspect in depth. The results showed that the level of student learning independence was included in the high criteria where the average overall percentage score was 67.604%. The results of this study are expected to be an evaluation material for subject teachers who organize distance learning in the future. In addition, both teachers and students must make preparations before carrying out the learning process, in order to achieve the desired results.